2008
DOI: 10.1088/0953-2048/21/9/095004
|View full text |Cite
|
Sign up to set email alerts
|

The fabrication of YBa2Cu3O7−xfilm by metal–organic deposition using terpineol-modified trifluoroacetates

Abstract: Dense and homogeneous superconductive YBa2Cu3O7−x (YBCO) thin films were grown epitaxially on single-crystal LaAlO3 (LAO) substrates by a new MOD method with terpineol-modified trifluoroacetic solution. The YBCO precursor solution incorporated with terpineol enabled a remarkable decrease in the organic pyrolysis process. The YBCO films have an onset critical temperature of 90 K and Jc (77 K, 0 T) of 3.8 MA cm−2. The addition of terpineol was suggested to be responsible for the smoother and low-stressed YBCO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The narrowing of the decomposition temperature range could be verified by comparing DTA curves A and B in figure 9. Therefore, the decomposition reaction speed during the pyrolysis process was promoted by PEG addition, which was different from the broadening of the decomposition temperature range using terpineol additive by Ding et al [34].…”
Section: Thermal Analysis and Mechanical Property Measurementsmentioning
confidence: 86%
“…The narrowing of the decomposition temperature range could be verified by comparing DTA curves A and B in figure 9. Therefore, the decomposition reaction speed during the pyrolysis process was promoted by PEG addition, which was different from the broadening of the decomposition temperature range using terpineol additive by Ding et al [34].…”
Section: Thermal Analysis and Mechanical Property Measurementsmentioning
confidence: 86%
“…In order to overcome this limitation, several advanced MOD methods have been developed in recent years [17][18][19][20][21]. In our previous work [22], various precursor solutions with different fluorine contents have been tested, including the conventional low-fluorine (CLF) solution with a fluorine content of 54% (F-54%), the super low-fluorine (SLF) solution (F-31%), and the extremely-low-fluorine…”
Section: Introductionmentioning
confidence: 99%
“…For the TGA curves (inset in figure 2), the mass loss of PAn or PAnD sample initialized at about 200 • C, and completed at about 320 • C. Thus the decomposition temperature range of PAn and PAnD samples could be estimated as about 120 • C, which was also broader than that of the conventional TFA solution sample (about 80 • C). The broadening of the decomposition temperature range was also found in the study of terpineol additive by Ding et al [16]. They suggested that this phenomenon could be related to the alleviation of stress generated during the decomposition reactions, thus smooth films could be obtained after a rapid pyrolysis step.…”
Section: Resultsmentioning
confidence: 54%
“…Such a long pyrolysis step is designed because strong internal stresses accompany the decomposition reactions, and buckling or cracking might occur such that the final YBCO films are degraded [10,11]. In order to shorten the pyrolysis time, various improvements of the precursor solution preparation have been proposed in the past decade, such as lowering the fluorine content [12][13][14], using organic additives [15][16][17], and using trifluoroacetic anhydride (TFAA) [18]. Low-fluorine solution has been proven efficient by many groups, because the generation of fluorine-related gases could be reduced and the stress could be alleviated [12].…”
Section: Introductionmentioning
confidence: 99%